Symmetry Relations in the Structure of Eu te amo, by Antonio Carlos Jobim and Chico Buarque de Holanda (Orfeu, 2021)
This article proposes a detailed analysis of the pitch structure of the song Eu te amo, composed by Antônio Carlos Jobim and Chico Buarque de Holanda, through the combined action of the Schenkerian methodology (properly adapted to the conditions of the object of study) and tools from the so-called Post-Tonal Theory. It aims to highlight the complex relationships of symmetry that characterize the piece, which involves the interaction of the interval classes 1, 5 and 6. After an analytical evaluation of the lyrics and the poetic form, which establishes a basis for the subsequent examination of the correlations between music and text, the article presents a discussion of the problems associated with the use of Schenkerian theory in post-tonal and popular music, supported by the literature on these subjects (STRAUS (1987), LERDAHL (1989), FORTE (1995), McGOWAN (2008), LARSON (1998; 2009), among others). The analysis that follows reveals the extraordinary symmetrical infrastructure (projected at different levels of organization) on which the song is built, which includes interactions with the poetic argument. In conclusion, although not perfectly adjusted to the models of the Schenkerian Ursatz, the complex and layered structure of the piece has its own logic, consistent in relation to examples of similar nature in the Jobinian work.
Keywords: Intervallic symmetry; Jobim and Chico Buarque; Schenkerian analysis in popular music; Relationship between text and music